Simulation of Acoustic Conditions within the Markanda Temple, India - Apoorva A Dandge; Akshay P. Patil (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The ancient religious structures hold a significant wealth of knowledge, with their acoustics being a part of their inheritance. Hindu temples in Central India built during the 12th century exemplify this. However, the challenge lies in evaluating the acoustics under occupied conditions due to the various configurations of sound sources and worshippers' positions. While existing literature offers calculation methods for predicting reverberation time, this paper introduces a novel and intriguing approach. We simulate the acoustics in the pavilion and sanctum space under occupied conditions using the advanced acoustics simulations software ‘ODEON’. This innovative method allows us to obtain a comprehensive set of acoustic parameters. Due to its reverberant nature, the study examines the Markanda temple in Gadchiroli district, allowing for a better understanding of occupancy-related variations. Nevertheless, the results indicate that the impact of occupancy was limited due to the absorbing elements on the floor in the form of carpet, resulting in ‘fair’ acoustic conditions for speech intelligibility.